Transformative-Critical Education Paradigm: Investigating the Influence of Paulo Freire and Moeslim Abdurrahman in Ikatan Pelajar Muhammadiyah (1998-2008) - Khoirudin, Azaki (Muhammadiyah University Press, 2017)
This study investigated the influence of Paulo Freireâs criticaleducation and Moeslim Abdurrahmanâs Transformative Islam in IkatanPelajar Muhammadiyah (IPM). The problem statement was formulated:to what extent Freire and Moeslim influence the educational thoughtand practice of education in IPM? By using discourse analysis, thisstudy revealed that the discourse and practice of critical-transformativeeducation has evolved in IPM since the reform era in 1998-2008.The Discourse of critical education and Transformative Islam areintertwined into âManifesto of Transformative Critical Movementâincorporated in the educational guideline of IPM members. Thistransformative-critical discourse has encouraged IPM becoming apopulist student organization. Afterward, the discourse and practice ofthis organizationâs movements is accentuated by the criticism towardsinjustice and the struggle towards social transformation